JNK modifies neuronal metabolism to promote proteostasis and longevity. Issue 3 (27th February 2019) - Wang, Lifen; Davis, Sonnet S.; Borch Jensen, Martin; Rodriguez‐Fernandez, Imilce A.; Apaydin, Cagsar; Juhasz, Gabor; Gibson, Bradford W.; Schilling, Birgit; Ramanathan, Arvind; Ghaemmaghami, Sina; Jasper, Heinrich
Abstract: Aging is associated with a progressive loss of tissue and metabolic homeostasis. This loss can be delayed by single‐gene perturbations, increasing lifespan. How such perturbations affect metabolic and proteostatic networks to extend lifespan remains unclear. Here, we address this question by comprehensively characterizing age‐related changes in protein turnover rates in the Drosophila brain, as well as changes in the neuronal metabolome, transcriptome, and carbon flux in long‐lived animals with elevated Jun‐N‐terminal Kinase signaling. We find that these animals exhibit a delayed age‐related decline in protein turnover rates, as well as decreased steady‐state neuronal glucose‐6‐phosphate levels and elevated carbon flux into the pentose phosphate pathway due to the induction of glucose‐6‐phosphate dehydrogenase (G6PD). Over‐expressing G6PD in neurons is sufficient to phenocopy these metabolic and proteostatic changes, as well as extend lifespan. Our study identifies a link between metabolic changes and improved proteostasis in neurons that contributes to the lifespan extension in long‐lived mutants.